Bactericidal Effects of Snake Venom Phospholipases A2: A Systematic Review and Analysis of Minimum Inhibitory Concentration - Zainab Umar Abdullahi; Salihu Sabiu Musa; Hammoda Abu-Odah; Ayman Ahmed; Abdulmalik Ahmad Lawan; Umar Muhammad Bello (Physiologia, 2023)
Background: Infections caused by multi-drug resistance (MDR) strains are potentially fatal public health issues worldwide that need pressing attention. Previous reports suggested using snake venom fractions as an effective alternative mechanism to the already available antibacterial drugs. In this study, we conducted a systematic review to analyze the bactericidal effects of snake venom phospholipases (PLA2s). Methods: From the beginning through 30 March 2022, we searched the PubMed and Embase databases in accordance with the most recent PRISMA recommendations. We also conducted a manual search to identify relevant reports to improve literature coverage. Results: A total of 24 studies were included based on the selection criteria to compile this review. Of them, 16 studies were obtained from the abovementioned databases and eight through manual searches. The other 8 studies were obtained through the references of the included studies. According to the review, we reported that some PLA2s showed more vigorous bactericidal activity on some Gram-negative and a moderate effect on Gram-negative and Gram-positive. Furthermore, we reported that the presence of p-bromophenacyl bromide (p-BPP) showed a significant decrease in enzymatic and associated antibacterial activities. Moreover, we observed that about 80% of the PLA2s reported in our systematic review study were those from the Viperidae family, whereas 20% came from the Elapidae family. Moreover, some variations were revealed in the current study regarding the mechanism of actions of the snake venom PLA2s (svPLA2s). Conclusion: This systematic review provides a comprehensive overview of the bactericidal effect of snake venom PLA2s and the analysis of the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of PLA2s for bacterial strains. Varying bactericidal effects from various snake species and South American rattlesnakes were reported, presenting compelling concepts to the alternative search for therapies against bacterial resistance. Thus, further analysis of the bactericidal effects of other snake venoms PLA2s considering different strains is needed. Moreover, more data are needed to investigate other bacteria of public health priority using peptides and other purified snake toxins.